From high school to community college to ODU to the C-suite: creating a text-book free pathway to a bachelor's Z-degree. (2nd January 2023) - Draper, Darryl; Mayes, Lisa; Payne, Brian
ABSTRACT: To counter tuition and textbook costs for degree-seeking students, a specific pathway to a bachelor's degree in Leadership was developed. The pathway, comprised of partnerships with the high school Leadership Academy at a public high school, community college, and Old Dominion University (ODU), reduced tuition and textbook costs, allowing the completion of the Leadership major textbook-free using Open Educational Resources (OER). The three partners established the infrastructure necessary to expand the delivery of textbook-free courses, by recruiting and providing OER training for faculty and teachers. Eight high school teachers and eighteen ODU faculty participated in OER training. In addition, ODU developed supplemental OER training to support their faculty. Since Summer 2017, the Leadership Academy enrolled 364 high school students with 207 completing 349 dual- enrolment courses with many of the students enrolled in multiple courses. While the Leadership Academy and CC students have not yet matriculated, the Leadership major has already gained noted success for students. Within three semesters, students saved approximately 113, 000 (based on 936 course registrations), in textbook costs for the Interdisciplinary Studies (IDS) major in Leadership. At the high school, students taking dual-enrolment courses with a community college saved approximately 230, 640 in tuition costs. As the program matures it will have a direct and profound impact on first-generation, low-income, and underrepresented students in the Commonwealth. For students who earn a bachelor's degree through this pathway, it is possible that the full tuition for the degree could be as low as 16, 725. The textbook costs for students through this pathway could be reduced from an average cost of 5, 000 to zero.